PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB), BELANJA PEMBANGUNAN DAN JUMLAH TENAGA KERJA TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN/KOTA DI JAWA TENGAH (Studi Kasus Pada Pemerintah Kabupaten/Kota Di Jawa Tengah) - Ria Mustika Sari, 11.05.52.0092; Darso, Maryono (Students Journal of Accounting and Banking, 2015)
The aim of study is to find out either or not Gross Region Domestic Product, Capital Expenditure and Total Employment influence the Local Revenue District and Cities in Central Java.Population inthis study is District and Cities in Central Java. The sample in this study was done by using purvosive sampling.The sample in this study is 35 District and Cities in Central Java. The data used in this study from 2011 to 2013. The data of this study is secondary of realization of local government budgets. Based on the test results indicate that Region Domestic Product influences the Local Revenue both positively and significantly, Capital Expenditure doesnât influence the Local Revenue and Total Employment in this study influences negatively and significanntly to Local Revenue. Simultaneously of Gross Region Domestic Product, Capital Expenditure and Total Employment influence the Local Revenue.Keywords: Gross Region Domestic Product, Capital Expenditure, Number of Workes and Local Revenue